From "Time is Brain" to "Imaging is Brain": A Paradigm Shift in the Management of Acute Ischemic Stroke. Issue 5 (10th February 2020) - Puig, Josep; Shankar, Jai; Liebeskind, David; Terceño, Mikel; Nael, Kambiz; Demchuk, Andrew M; Menon, Bijoy; Dowlatshahi, Dar; Leiva‐Salinas, Carlos; Wintermark, Max; Thomalla, Götz; Silva, Yolanda; et al.
ABSTRACT: Arterial recanalization to restore the blood supply and limit the brain damage is the primary goal in the management of acute ischemic stroke (AIS). Since the publication of pivotal randomized clinical trials in 2015, endovascular thrombectomy has become part of the standard of care in selected cases of AIS from large‐vessel occlusions up to 6 hours after the onset of symptoms. However, the association between endovascular reperfusion and improved functional outcome is not strictly time dependent. Rather than on rigid time windows, candidates should be selected based on vascular and physiologic information. This approach places imaging data at the center of treatment decisions. Advances in imaging‐based management of AIS provide crucial information about vessel occlusion, infarct core, ischemic penumbra, and degree of collaterals. This information is invaluable in identifying patients who are likely to benefit from reperfusion therapies and excluding those who are unlikely to benefit or are at risk of adverse effects. The approach to reperfusion therapies continues to evolve, and imaging is acquiring a greater role in the diagnostic work‐up and treatment decisions as shown in recent clinical trials with extended time window. The 2018 American Heart Association/American Stroke Association guidelines reflect a paradigm shift in the management of AIS from "Time is Brain" to "Imaging is Brain." This review discusses the essential role of multimodal imaging developing from recent trials on therapy for AIS.